1998
DOI: 10.1021/es980127c
|View full text |Cite
|
Sign up to set email alerts
|

Natural Formation of Chloroform and Brominated Trihalomethanes in Soil

Abstract: We studied the occurrence of halogenated organic compounds in soil air of rural areas. Chloroform appeared to occur in elevated concentrations compared to those in atmospheric air, while the concentrations of other chlorinated solvents were almost equal or lower than those in atmospheric air. We report conclusive evidence that chloroform is naturally produced from in situ Na37Cl enrichment field studies in soil top layers. The concentration of chloroform in soil air increased in deeper soil layers, but spiking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 20 publications
3
71
0
2
Order By: Relevance
“…CHBr 3 has been found in the air of upper soil of a pristine spruce forest (Haselmann et al, 2000). However in soil air of rural areas, Hoekstra et al (1998) found no detectable concentrations of CHBr 3 , except after in-situ enrichment by KBr. This suggests the potential of soils containing elevated bromide, e.g.…”
Section: Introductionmentioning
confidence: 88%
“…CHBr 3 has been found in the air of upper soil of a pristine spruce forest (Haselmann et al, 2000). However in soil air of rural areas, Hoekstra et al (1998) found no detectable concentrations of CHBr 3 , except after in-situ enrichment by KBr. This suggests the potential of soils containing elevated bromide, e.g.…”
Section: Introductionmentioning
confidence: 88%
“…A variety of volatile organochlorines (VOCls), such as chloroform, is produced in soil (Hoekstra et al, 1998;Keppler et al, 2002;Svensson et al, 2007b;Rhew et al, 2008;Albers et al, 2010). VOCls are also emitted by wildfires, geothermal sources (Lobert et al, 1999), marine sources (Laturnus et al, 1998), and plants in temperate forest ecosystems (Forczek et al, 2015).…”
Section: Input and Export From Vegetationmentioning
confidence: 99%
“…9,10 Different pathways have been proposed for natural chloroform production. When incubating organic compounds (organic acids, glucose) with chloroperoxidase and hydrogen peroxide, chloroform was detected as the main reaction product.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another proposed pathway is the formation of chloroform by decarboxylation of trichloroacetic acid that is itself product of chlorination of organic matter in soil or originates from atmospheric oxidation of chlorinated ethenes. 9 Recently, it was demonstrated that chloroform can also be produced from organic model substance in a Fenton-like process in the absence of chloroperioxidases. 15 For groundwater management and remediation, it is important to know to what extent chloroform in groundwater originates from natural sources.…”
Section: ■ Introductionmentioning
confidence: 99%